2017
DOI: 10.1136/bjsports-2016-097270.158
|View full text |Cite
|
Sign up to set email alerts
|

Assessing knowledge and attitudes towards concussion in irish footballers

Abstract: ObjectiveTo assess current levels of knowledge and attitude towards concussion in Irish soccer players and compare findings with other athletic groups. DesignParticipants completed a paper bases Rosenbaum Concussion Knowledge and Attitude Survey (RoCKAS). Results were collated and analysed using descriptive statistics to look for correlation between player subgroups.SettingUCD AFC training facility, Dublin, Ireland.ParticipantsSeventy male semi-professional and amateur League of Ireland players. Participants h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
1
7
1
Order By: Relevance
“…The mean CKI in this study was found to be 56.2% which was less than those studies using English professional footballers (65.6%; Williams et al, 2016), Irish semi-professional and professional footballers (74.8%; Gallagher & Falvey, 2017), Canadian youth soccer players (78%; Doucette et al, 2021), amateur South African rugby players (75%; Viljoen et al, 2017) and cyclists from all global regions (75.8%; Hurst, Novak, Cheung, & Atkins, 2019). The findings of inadequate awareness of concussion causes, diagnosis and sequelae in this population specifically may be indicative of the fact that concussion research and public knowledge translation has been primarily focused on developed countries (Eagles et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…The mean CKI in this study was found to be 56.2% which was less than those studies using English professional footballers (65.6%; Williams et al, 2016), Irish semi-professional and professional footballers (74.8%; Gallagher & Falvey, 2017), Canadian youth soccer players (78%; Doucette et al, 2021), amateur South African rugby players (75%; Viljoen et al, 2017) and cyclists from all global regions (75.8%; Hurst, Novak, Cheung, & Atkins, 2019). The findings of inadequate awareness of concussion causes, diagnosis and sequelae in this population specifically may be indicative of the fact that concussion research and public knowledge translation has been primarily focused on developed countries (Eagles et al, 2016).…”
Section: Discussioncontrasting
confidence: 85%
“…A mixed-methods study by Williams et al (2016) noted an average concussion knowledge score of 65.6% amongst English professional footballers. A slightly higher mean score (74.8%) was found in a cross-sectional study of Irish amateur and semi-professional players (Gallagher & Falvey, 2017). Similarly, in a study including junior soccer player in Canada, knowledge was on average 78.8% using the Rosenbaum Concussion Knowledge and Attitudes Survey student version (RoCKAS-ST) (Doucette, Du Plessis, Webber, Whalen, & Garcia-Barrera, 2021).…”
Section: Introductionmentioning
confidence: 83%
“…5154 The most common tool utilised in previous studies is the Rosenbaum Concussion Knowledge and Attitudes Survey (RoCKAS), a reliable psychometric measure that provides an understanding of the respondent’s knowledge about and attitude towards concussion. 55 The RoCKAS has been previously validated as a reliable measure for CK in collegiate student athletes 56 and has also been used extensively to measure CK and CA in students 55–59 and athletes of various sporting backgrounds including ice hockey, 59 , 60 soccer, 61 , 62 and football 54 , 63 .…”
Section: Introductionmentioning
confidence: 99%
“…The RoCKAS is a psychometrically analyzed and verified survey which assesses the knowledge and attitudes of individuals pertaining to concussion [19]. This survey has been utilized by other studies to reliably assess knowledge and attitudes about concussion since its publication [20][21][22][23][24]. The survey analyzes three indices: Concussion Knowledge Index (CKI), Concussion Attitude Index (CAI), and the Validity Scale (VS).…”
Section: Instrumentmentioning
confidence: 99%